Human–Human Handover Tasks and How Distance and Object Mass Matter. Issue 1 (February 2017) - Hansen, Clint; Arambel, Paula; Ben Mansour, Khalil; Perdereau, Véronique; Marin, Frédéric
We investigated the coordination between two individuals during object handovers. Ten participants (eight males, two females; 26.0 ± 5.0 years, 72.7 ± 13.5 kg, 1.73 ± 0.8 m) arranged in pairs (a giver and a receiver), passed an object from the giver to the receiver at a self-selected speed. A motion capture system quantified the giver and the receiver's motion simultaneously. Three interpersonal distances and three object masses were chosen to study the handover. We hypothesized that (a) the handover occurs at half of the interpersonal distance between the giver and receiver and (b) the handover height depends on the objects' mass. Taken together, our results show that the handover strongly depends on the interpersonal distance between the giver and receiver, while object mass related only to handover duration.